Assessing local farmer’s perspectives on the role of bat in providing ecosystem services in the Batang Toru ecosystem, North Sumatra, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Harahap HA, Yonariza. 2022. Assessing local farmer’s perspectives on the role of bat in providing ecosystem services in the Batang Toru ecosystem, North Sumatra, Indonesia. Biodiversitas 23: 4322-4328. Bats play an important role as pollinators in maintaining the ecosystem services and improving the local economy in Batang Toru Ecosystem (BTE). However, the anthropogenic impacts negatively affect their sustainability, making the evaluation of their services increasingly needed. This study was conducted to examine the local farmers’ action against bats in BTE. The objectives were to analyze: (1) farmers’ knowledge of the role of bats in ecosystem services, (2) the perception of bats, (3) awareness of bat population loss and its impact on durian production, and (4) farmers' actions against bats on their land. The results showed that 1 out of 7 farmers exhibited negative actions toward bats in their agroforest lands. They also had significantly low knowledge about bat services in agroforestry. Most farmers regarded bats as meat for food and medicine rather than as pollinators of durian fruits. We recommend that the government and conservation institutions carry out initiatives to educate farmers regarding the importance of bat services, and conservation efforts should be made to maintain the viable population of bats.